2012
DOI: 10.1021/ie201757t
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling of Multistage Multiproduct Batch Plants Operating in a Campaign-Mode

Abstract: In this work, mixed integer linear programming models for scheduling multistage multiproduct batch plants operating under campaign mode are proposed. It is assumed that each plant stage includes identical parallel units operating out of phase. Given the plant topology and the number of batches of each product to be processed in the campaign, the objective is assigning batches to units in each stage in order to minimize the cycle time of the campaign. An asynchronous slot-based continuous-time representation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Also, according to the rule recently mentioned, in stage 1, slots 2 and 3 are only used on unit 1, slots 1, 5, and 6 are used on unit 2, and slots 4 and 7 are only used on unit 3. This preordering constraint in the assignment of batches to slots has been used by Fumero et al , where the authors have shown that this rule can be considered a good heuristic strategy for solving scheduling problems.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Also, according to the rule recently mentioned, in stage 1, slots 2 and 3 are only used on unit 1, slots 1, 5, and 6 are used on unit 2, and slots 4 and 7 are only used on unit 3. This preordering constraint in the assignment of batches to slots has been used by Fumero et al , where the authors have shown that this rule can be considered a good heuristic strategy for solving scheduling problems.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…In practice, it is common to select a set of production resources to define a production line that will operate during a certain time period, sufficient to supply a given demand. More recently, Fumero et al (2012) presented a solution approach for the scheduling of multistage multiproduct batch plants. They first solve a simplified slot-based continuous -time formulation that involves preordering constraints for the assignment of batches to slots in each stage.…”
Section: Scheduling Of Multipurpose Batch Plantsmentioning
confidence: 99%
“…Fumero, Corsano, and Montagna () proposed models based on MILP for scheduling of a multistage multiproduct batch plant with identical parallel units, operating in a campaign mode.…”
Section: Introductionmentioning
confidence: 99%